Principles of Stochastic Generation of Hydrologic Time Series for Reservoir Planning and Design: A Case Study. - Guimarães, Rita Cabral (2012)
Simulation has been an important tool for planners in many fields of knowledge. In the field of water resources the uncertainties due to unknown data population and the short length of the records work together to make the simulation especially important. The major utilization of water resources at the level needed in modern society makes water storage essential for satisfying the demand. Therefore, the need to reduce the uncertainty in the design of water storage capacity is an important problem in the field of water resources utilization. This problem can only be satisfactorily solved with the aid of simulation. On the other hand, the implementation of adequate exploration politics also needs to use simulations in order to obtain results with low uncertainty. In simulation of water resources systems the use of synthetic time series is a current practice. In this study the number of generated time series to use in the problems described are analyzed. Annual and monthly synthetic flows were generated preserving the relevant statistics of the available historical data and then the number of time series to generate was determined. The results of the case studies indicate that the proposed methodology is a plausible approach to solve the analyzed problem and lead to the conclusion that the number of time series to generate should be 1200.